Facile synthesis of high‐molecular‐weight acid‐labile polypeptides using urethane derivatives. Issue 2 (22nd July 2014) - Wong, Shirley; Kwon, Young Jik
ABSTRACT Polypeptides have received noticeable attention in the biomedical field due to their structural versatility and biomimetic properties. Particularly, polypeptides that are responsive to biological stimuli, such as mildly acidic extracellular and intracellular conditions, have great potential as delivery carriers for therapeutics. However, synthesis of high‐molecular‐weight acid‐labile peptides is often daunting due to highly restrictive polymerization conditions and limitations in preserving acid‐degradable functional groups. For instance, the popular N‐carboxyanhydride (NCA) ring‐opening polymerization (ROP) is efficient, but acid‐labile NCA monomers are difficult to synthesize and store. In this study, acid‐labile polypeptides with high molecular weights were synthesized under mild, permissive conditions using carboxylated urethane derivative monomers which are stable for ease of handling. The polymerization was successful in various organic solvents at room temperature, and did not require additional energy or initiation to drive the formation of NCA intermediates. The polymerization was also rapid enough to be independent of inert atmosphere. The strategy explored here to synthesize high‐molecular‐weight acid‐labile polypeptides offers significant advantages including facile synthesis of acid‐labile urethane derivative monomers that are stable, even in contact with moisture, and fast polymerization under easily achievable conditions. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 280–286